Evolution of Technical Education in Colonial India: A Historical Perspective - N. , Dhaivamsam (International Journal of Psychosocial Rehabilitation, 2020)
The present study attempts to explore the historical development of technical education in India specifically from 1902 to 1947, a period marked by significant changes and advancements. The article explores the various phases of technical education during this time frame, shedding light on its growth, challenges, and crucial moments. The early 20th century witnessed a growing awareness of the importance of technical education in India, driven by initiatives such as the Indian Institute of Science established by philanthropist Jamshedji Tata in 1909-22. The period also saw the establishment of engineering colleges, schools, and institutes across the country, indicating a shift towards prioritizing technical education. The Study explores the Indian Education Policy of 1902, which played a crucial role in the rapid expansion of technical education. Notably, recommendations from various education committees, including the Hartog Committee Report and Sargent Committee Report, aimed to improve the conditions of technical education in India. The research discusses the growth of technical institutions at different levels, including Industrial Training Institutes (ITIs), Polytechnic Institutes, and Engineering Colleges. The statistics presented in tables demonstrate the proliferation of technical and industrial schools during this period. The study emphasizes the role of the All India Council for Technical Education (AICTE) and the Scientific Manpower Committee (SMC) in shaping the development of technical education in India.